PWE-030 Sigmoidoscopy both delays time to diagnosis and has poor diagnostic utility for paediatric-onset inflammatory bowel disease. (23rd September 2015) - Dart, R J; Russell, R K; Read, J R; Rogers, P; Gillett, P M; Wilson, D C
Abstract : Introduction: A significant proportion of inflammatory bowel disease (IBD) presents in childhood and adolescence, a critical time for growth and development, so timely diagnosis is desirable to ensure patients achieve their growth potential. Our aim was to delineate factors including referral pathway and endoscopic investigation that may delay diagnosis in paediatric-onset IBD (PIBD). Methods: We performed a retrospective case note review in a tertiary PIBD centre from 1996–09. Symptom onset was defined as the length of history of presenting complaint; date of presentation was defined as the first presentation, often to primary care. Date of each referral, to whom, and the investigations carried out by each discipline before either diagnosis or onward referral were recorded. Date of diagnosis is defined as the date of the endoscopy providing definitive histological diagnosis. Statistical analysis was performed with Excel. Result: 166 PIBD patients with a median (range) age at diagnosis of 11.5 (2–17) years: 58% had Crohn's disease, 24% had ulcerative colitis and 18% had indeterminate colitis. Median time from first symptoms to diagnosis was 27.5 weeks (2–445) and from first referral to diagnosis was 14 (0–439) weeks. Median (range) time to diagnosis from referral was faster when first referral was made to medical paediatrics in contrast to surgical services at 11 (0–341) vs 33 (0–439) weeks (p=0.001). 23% of patients underwent sigmoidoscopy prior to diagnosis, 12% colonoscopy alone and 67% colonoscopy+upper GI endoscopy (UGIE). 76% of sigmoidoscopies, performed in isolation, were performed by surgeons, whereas 97% of colonoscopy+UGIE were performed by paediatric GI services; sigmoidoscopy diagnosed IBD on 55% of occasions whereas colonoscopy+UGIE diagnosed IBD on 99% of occasions (p=0.0001). Colonoscopy alone was diagnostic on 80% of occasions, inferior to colonoscopy and UGIE (p=0.002). Median time to PIBD diagnosis when sigmoidoscopy was performed prior to diagnosis was significantly longer than for patients who had no sigmoidoscopy performed, at 29.5 (1–402) vs 12 (0–439) weeks (p=0.005). Conclusion: Use of sigmoidoscopy as opposed to colonoscopy+UGIE was associated with delayed PIBD diagnosis. We suggest that sigmoidoscopy should be abandoned in the diagnosis of PIBD, and Colonoscopy and UGIE is the endoscopic investigation of choice, supporting the "Porto criteria" for PIBD diagnosis. 1